Wo ji hu kan dao gun gun chen ai / selected poetry of Yu Xiang. - Yu, Xiang (Jintian series of contemporary literature., 2013)
Considered a representative figure of the post-1970s Chinese poets, Yu Xiang is part of a new generation of contemporary Chinese poets following in the footsteps of the "Obscure" (otherwise known as "Misty") poets and the post-"Obscure" writers. If identification is indeed a shadow act of figuration, Yu Xiang does not care for any post-age or post-modern label. Her response toward specific social or political realities in China during these recent years differ from her predecessors' during their respective epochs, in the sense that she does not necessarily depict them from an oblique stance. She does not merely dwell in ambiguities, contradictions and ambivalence. Nor does she present her work as a purely journalistic understanding of the downtrodden: impoverished villagers, traumatized mothers who lost children during the collapse of "tofu-skin" schools during the 2008 Sichuan earthquake. Instead, she depicts characters with a comparative eye--not just as a witness--but also from the starting point of having "felt a feeling," an epiphany. Unafraid of going near politically radioactive realities and histories, Yu Xiang is least interested in scoring ideological points, or telling "her" side of a narrative, be it as an artist or a social critic. At first read, each of Yu Xiang's poems comes across as an intimate address with a personal touch. Through poetry, she seeks a specific reader and listener, while being a reader and listener herself. She is interested in peeling silence with verses